Education and employment in two Chilean undergraduate programs. Issue 3 (26th March 2019) - Espinoza, Oscar; McGinn, Noel; González, Luis; Sandoval, Luis; Castillo, Dante
Abstract : Purpose: The purpose of this paper is to determine which of the two variables would be a more reliable proxy for quality of university training: graduates' satisfaction with their degree program, or institutional prestige. Design/methodology/approach: Graduates of professional psychology and teaching programs from three Chilean universities responded to a questionnaire asking their perception of different aspects of their degree program and experiences in their first employment. The three universities differ significantly in the proportion of applicants admitted, and in their prestige. Findings: Salary levels are highly related to profession, but unrelated to graduates' ratings of quality of curriculum or teaching methods. Overall satisfaction with the university experience is not linked to job satisfaction. Job satisfaction, on the other hand, is highly influenced by salary and secondarily by instructional practices and perceived work relevance of the degree program. Research limitations/implications: This study is based on data from 3 of Chile's 60 universities, and graduates of two programs. Most employment in the two professions is regulated by labor agreements. Generalizability of results is limited. Graduates may not have been employed enough to demonstrate their capacities. Practical implications: The findings offer more evidence that prestige ratings are an unreliable indicator of the quality of formation offered by universities. If the government seeks to reduce income inequality, public subsidies of higher education should be based on program quality rather than on institutional prestige. Originality/value: The findings are directly relevant to the current debate in Chile about what might and what might not help to reduce severe economic inequality.